Design and Analysis of All Optical Logic Gates Based On 2-D Photonic Crystals - Rani, Deeksha (My University, 2015)
Photonic crystal is artificially designed optical material in which dielectric constant changed periodically. Due to their unique properties, the photonic crystal based logic gates have numerous advantages over the conventional logic gates such as compactness, simple structure, high speed and high confinement. The size of optical logic gate based on photonic crystal is in the order of wavelength. The photons are not affected by the external disturbance; it results in low transmission losses. There are some wavelengths which do not propagate through the structure and form the photonic band gap. By engineering the photonic band gap, the flow of light can be controlled. These logic structures are key component of optical network and optical communication system. Because of various advantages, it is favorable for use of future optical signal processors and optical computers. The objective of this dissertation is to analyze the performance of 2-D photonic crystal based all optical logic gates and for this purpose Opti-FDTD software is used which allows the design of various configurations of photonic crystal structures. Firstly, a simple design of optical logic OR gate is presented for the application of switching as it has high extinction ratio. This structure is compact as well as suitable to design other optical circuits. Secondly, all optical logic NOR gate is designed based on two cross waveguides structures. These cross waveguide structures are optical NOT and OR gate. The parameter of structure (NOT and OR gate) is optimized by iterative process. These optimized structures have high contrast ratio. Thirdly, a simultaneous implementation of NOT and AND gate to design optical NAND logic gate without using any external device. These structures are compact in size and have high contrast ratio compared to the earlier reported work. For practical applications, analyze the fabrication error tolerance of NAND gate. These structures are simple to fabricate; so it is favorable for use of future optical communication system and signal processor.
M.E. (ECED)
Keywords: PC; PBG; Logic Gates; Defects; ECED